AN AGENCY THEORY APPROACH TO DISINTERMEDIATION IN THE MICE DISTRIBUTION CHANNEL FROM THE PERSPECTIVE OF THE HOTEL INDUSTRY - Rojas, Alberto; Reardon, Emma (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2022)
MICE Tourism is a segment of the tourism industry that deals with the organisation of Meetings, Incentives, Conventions and Exhibitions, which are experiencing a major process of disintermediation. This article applies the principal-agent problem in the theory of agency to analyse MICE disintermediation. It uses a dominant/sequential qual-QUAN mixed methods approach. Firstly, through interviews with MICE professionals to validate the research variables, test sample and questionnaire. Then, quantitative research using a survey sent to 365 MICE stakeholders in Europe. The opinions of hoteliers were compared with those of other MICE stakeholders to analyse disintermediation and determine the role of hoteliers in this new scenario. Our findings confirm a trend of partial disintermediation in which hotel bookings are the most disintermediated service and hoteliers are the stakeholders that pose a more proactive and aggressive attitude towards disintermediation. This paper is of interest for MICE stakeholders to better understand their position in the value chain and interpret the process of disintermediation. Its originality is based on the fact that it gathers the opinions of all MICE agents with a special focus on the perspective of its most dominant actor: the hotel.